Somatodendritic accumulation of Tau in Alzheimer's disease is promoted by Fyn‐mediated local protein translation - Li, Chuanzhou (EMBO J, 2017)
The cause of protein accumulation in neurodegenerative disease is incompletely understood. In Alzheimer's disease (AD), the axonally enriched protein Tau forms hyperphosphorylated aggregates in the somatodendritic domain. Consequently, a process of subcellular relocalization driven by Tau phosphorylation and detachment from microtubules has been proposed. Here, we reveal an alternative mechanism of de novo protein synthesis of Tau and its hyperphosphorylation in the somatodendritic domain, induced by oligomeric amyloid‐β (Aβ) and mediated by the kinase Fyn that activates the ERK/S6 signaling pathway. Activation of this pathway is demonstrated in a range of cellular systems, and in vivo in brains from Aβ‐depositing, Aβ‐injected, and Fyn‐overexpressing mice with Tau accumulation. Both pharmacological inhibition and genetic deletion of Fyn abolish the Aβ‐induced Tau overexpression via ERK/S6 suppression. Together, these findings present a more cogent mechanism of Tau aggregation in disease. They identify a prominent role for neuronal Fyn in integrating signal transduction pathways that lead to the somatodendritic accumulation of Tau in AD.